Coal home heating and environmental tobacco smoke in relation to lower respiratory illness in Czech children, from birth to 3 years of age - Baker, Rebecca J; Hertz-Picciotto, Irva; Dostál, Miroslav; Keller, Jean A; Nozicka, Jiri; Kotesovec, Frantisek; Dejmek, Jan; Loomis, Dana; Srám, Radim J (Environmental health perspectives, 2006)
OBJECTIVE: The objective of this study was to evaluate how indoor pollution from tobacco and home heating may adversely affect respiratory health in young children. DESIGN: A birth cohort was followed longitudinally for 3 years to determine incidence of lower respiratory illness (LRI). PARTICIPANTS: A total of 452 children born 1994-1996 in two districts in the Czech Republic participated. EVALUATIONS: Indoor combustion exposures were home heating and cooking fuel, mother's smoking during pregnancy, and other adult smokers in the household. Diagnoses of LRI (primarily acute bronchitis) from birth to 3 years of age were abstracted from pediatric records. Questionnaires completed at delivery and at 3-year follow-up provided covariate information. LRI incidence rates were modeled with generalized linear models adjusting for repeated measures and for numerous potential confounders. RESULTS: LRI diagnoses occurred more frequently in children from homes heated by coal [vs. other energy sources or distant furnaces ; rate ratio (RR) = 1.45 ; 95% confidence interval (CI) , 1.07-1.97]. Maternal prenatal smoking and other adult smokers also increased LRI rates (respectively: RR = 1.48 ; 95% CI, 1.10-2.01 ; and RR = 1.29 ; 95% CI, 1.01-1.65) . Cooking fuels (primarily electricity, natural gas, or propane) were not associated with LRI incidence. For children never breast-fed, coal home heating and mother's smoking conferred substantially greater risks: RR = 2.77 (95% CI, 1.45-5.27) and RR = 2.52 (95% CI, 1.31-4.85) , respectively. CONCLUSIONS: Maternal smoking and coal home heating increased risk for LRI in the first 3 years of life, particularly in children not breast-fed. RELEVANCE: Few studies have described effects of coal heating fuel on children's health in a Western country. Breast-feeding may attenuate adverse effects of prenatal and childhood exposures to combustion products.
Keywords: Infant; Male; lidé; Air Pollution, Indoor; Infant, Newborn; Humans; Smoking; novorozenec; bydlení; Tobacco Smoke Pollution; Child, Preschool; Czech Republic; znečištění tabákovým kouřem; znečištění vzduchu ve vnitřním prostředí; uhlí; mužské pohlaví; Housing; kojenec; Heating; Česká republika; ženské pohlaví; Coal; Female; vytápění; poruchy dýchání; Respiration Disorders; kouření; předškolní dítě